(untitled) - Pember, Don R. (Boston, 2005)
This book is about censorship of the press by the government, including courts which sustain the rights of individuals in civil actions, and the topic is covered pretty thoroughly.
Keywords: Mass media,Press law,Phương tiện truyền thông; Law and legislation,Luật và văn bản thi hành; United States,United States,Nước Mỹ